2022
DOI: 10.1093/jamia/ocac041
|View full text |Cite
|
Sign up to set email alerts
|

Developing a COVID-19 WHO Clinical Progression Scale inpatient database from electronic health record data

Abstract: OBJECTIVE There is a need for a systematic method to implement the World Health Organization’s Clinical Progression Scale (WHO-CPS), an ordinal clinical severity score for COVID-19 patients, to electronic health record (EHR) data. We discuss our process of developing guiding principles mapping EHR data to WHO-CPS scores across multiple institutions. MATERIALS AND METHODS Using WHO-CPS as a guideline, we developed the technica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…16 Although this scale has been used in several studies, to our knowledge, no study has applied AI and chest imaging to assess the severity proposed by the WHO. Ramaswamy et al 26 detailed the calculation of the WHO score from electronic medical records but did not use AI techniques or imaging. Bennett et al 27 used the WHO scale and grouped severity categories to predict clinical severity and found that demographics and comorbidities were correlated with disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…16 Although this scale has been used in several studies, to our knowledge, no study has applied AI and chest imaging to assess the severity proposed by the WHO. Ramaswamy et al 26 detailed the calculation of the WHO score from electronic medical records but did not use AI techniques or imaging. Bennett et al 27 used the WHO scale and grouped severity categories to predict clinical severity and found that demographics and comorbidities were correlated with disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…26 Secondary clinical outcomes included WHO-CPS score at day 7 and day 28, in-hospital mortality, ICU, hospital, and mechanical ventilation-free days at day 28. [26][27][28] WHO-CPS score was selected as it highlights patient progression throughout their disease course, highlighting key markers for critically ill patients such as requirement for mechanical ventilation, extracorporeal membrane oxygenation (ECMO), and vasopressor use.…”
Section: Discussionmentioning
confidence: 99%
“…48 In a bi-institutional study, health care systems automated data acquisition and clinical decision aid support to calculate the severity score for COVID-19 patients. 49 Daily, the system queried data from the institution's EHR and included demographic data, hospital length of stay, vital settings, ventilator settings, oxygen utilization, and dialysis use to produce a daily score. A time span of 13,386 patient days was analyzed and authors demonstrated successful implementation of such scoring system in 100% of inpatient days.…”
Section: Relevance Of Public Health Informatics To Perioperative Info...mentioning
confidence: 99%
“…A time span of 13,386 patient days was analyzed and authors demonstrated successful implementation of such scoring system in 100% of inpatient days. 49 While the mortality and morbidity benefit of these systems is still pending, this initiative demonstrates the ability of perioperative physicians to study the clinical characteristics of COVID-19 to contribute data and to recruit patients to trials across informatics platforms. Reeves et al 50 describe the implementation of an Incidence Command Center that helped identify EHR-based tools to support clinical care during a COVID-19 surge.…”
Section: Relevance Of Public Health Informatics To Perioperative Info...mentioning
confidence: 99%